Competency model for female project managers in the construction industry: a case study in Malaysia. (2016) - Jaafar, Mastura; Nuruddin, Azlan Raofuddin; Othman, Nur Liyana; Jalali, Alireza
The limited number of female project managers within the Malaysia construction industry suggests the pressing need of information relating to their competency. Further, it is the realisation that their contribution is crucial for transforming Malaysia into a developed country by 2020. Against this background, this study seeks to put forward a model assessing the female project managers' competency level. This study qualitatively tests the proposed framework, which quantitatively constructed based on several competency models introduced in previous literature. From the female perspective, findings highlight the project managers' equal competency level of both genders. Within the context of the Malaysian construction industry, the competency model for female project managers is proposed.